Pola Kerjasama Guru Dan Orang Tua Pada Masa Pandemi Covid 19 Di RA Masjid Agung Medan Polonia - Laila Wardati; Nurul Husna; Ade Khairunisa; Hagustina Lubis (Al-Ulum: Jurnal Pendidikan Islam, 2020)
: The purpose of this study was to analyze, (1) Problems of online learning at RA Masjid Agung Medan Polonia, (2) Collaboration patterns between parents and teachers in managing online learning at the Grand Mosque of Medan Polonia, and (3) obstacles faced in collaboration between teachers. and parents. The research method used in this research is a qualitative method based on descriptive studies. The results showed that. Some of the difficulties faced by parents in online learning are as follows: (1) Difficulty in identifying the behavior and initial characteristics of students, (2) Decreasing interest and motivation of children in learning, (3) Difficulty and minimal collaboration between parents and teachers, (4) ) Constrained by networks and internet facilities, (5) Problems in evaluating student learning outcomes, (6) Collaboration patterns between parents and teachers in managing online learning at the Grand Mosque of Medan Polonia. As for the pattern of cooperation between teachers and parents during online learning, there are two patterns, namely the permanent cooperation pattern and the tentative cooperation pattern. Meanwhile, the obstacles faced were (1) Difficulty communicating with parents outside school hours, (2) Constraints in understanding each other's conditions.Keywords: Learning, cooperation, Teacher, Parents